Politeness Strategies in English Directives: Empirical Evidence of Cross-Cultural Communication Among Indonesian and Malaysian Speakers - Afriani, Susi Herti; Astina, Ria; Said, Jamaliah; Alfi, Coky Fauzi; Novriani, Nadia (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Utterances constitute a fundamental form of communication in university settings, where students perform directive speech acts to request, instruct, or negotiate actions with peers, lecturers, and others. Although directives in English are widely used across academic contexts, their linguistic realizations vary across cultures. This study investigates politeness strategies in English directives among Indonesian (Palembangnese) English-speaking students (PSI) and Malaysian English-speaking students (MSM), two culturally related groups with potentially distinct pragmatic orientations. Employing a mixed-methods approach, the study integrates Written Discourse Completion Tasks and semi-structured interviews to examine both shared and divergent patterns. The findings indicate that while both groups employ common politeness markers (e.g., “please” and “thank you”) and are sensitive to contextual variables such as age, power, and social distance, they differ in their pragmatic orientations. PSI tend to emphasise expressions such as “excuse me” and respectful address terms, reflecting culturally embedded values of respect and religio-cultural influences, whereas MSM more frequently employ explicit expressions of gratitude, indicating a stronger orientation toward interpersonal management. These results highlight the role of cultural norms in shaping politeness as a reciprocal social practice. Despite its contributions, the study is limited to specific university contexts and age groups. Future research should include more diverse participants and longitudinal designs to capture the dynamic development of politeness strategies. Overall, understanding the cultural and linguistic dimensions of politeness is essential for enhancing cross-cultural communication, reducing misinterpretation, and fostering intercultural awareness in increasingly globalised academic environments.